Cross-Sector Collaboration in Intervention to Prevent and Reduce Stunting in Penajam Paser Utara District - Heryono Susilo Utomo; Thalita Rifda Khaerani; Yustisia Anzalna (Universitas of Muhammadiyah Makassar, 2023)
North Penajam Paser Regency is a locus of stunting area which is ranked 2nd highest in East Kalimantan Province with a score of 27.3. This study aims to find out the forms of cross-sectoral collaboration in interventions to prevent and reduce stunting in North Penajam Paser Regency which is expected to reduce the number of stunting cases. The type of research used is descriptive qualitative with data analysis techniques through observation, interviews, documentation and literature studies. Based on the results of the research, the program has run optimally so far, although it has not made any major changes in its handling. This is influenced by various constraints and obstacles such as cross-sectoral egos, insufficient budget, and people's mindset towards stunting making its implementation less effective in efforts to prevent and reduce stunting in North Penajam Paser Regency.